SÍNTESE DE LÍQUIDOS IÔNICOS APLICADOS NA DESSULFURIZAÇÃO DO DIESEL DE PETRÓLEO - Pinheiro, Renilma de Sousa (2014)
Among several energetic petroleum derivates diesel is responsible for a significant part of the fuel market since has been widely used for both domestic and industrial transportation. Unfortunately, its partial combustion generates harmful atmospheric emissions such as COx, NOx and SOx. Thus, this work aims to obtain [Morf]+[HCOO]- and [Nmorf]+[HCOO]- ionic liquids (IL) for the desulfurization of octane/benzothiophene model oil (BT) and commercial diesel (type-A). Therefore, all ionic solvents were synthesized by means of neutralization reaction, using Formic acid and amines (morpholine or n-methyl-morpholine), and characterized by FTIR and 1H RMN spectroscopies. Also, the sulfur removal efficiencies for model oil and diesel were estimated by CLAE and WDXRF techniques, respectively. For model oil + [Morf]+[HCOO]- system, sulfur removals of 75% (single extraction) and 99% (multiple extractions) were reached using 1:1 (sample:ionic solvent) and 30 min (extraction time). On the other hand, the model oil + [Nmorf]+[HCOO]- system, with 1:1 volumetric ration and 30 minutes leaded to 34% (single extraction) and 84% (multiple extraction) desulfurization. Conversely, for the commercial, the sulfur content were reduced in 34% (single extraction) and 47% (multiple extractions) if applied [Morf]+[HCOO]-, 1:1 volumetric ration and 30 min. Comparatively, the desulfurization carried out by the 1:3 volumetric ratio/30 min/single extraction method was rather equivalent the 1:3 volumetric ration/60 min/multiple extraction. Finally, the regeneration of the ionic liquid has reduced in approximately 9% the overall efficiency of the solvent after the fourth cycle extraction.